Association of Body Mass Index trajectory with thyroid nodules during young adulthood in China - Hang Yan; Su Yan; Jingfeng Chen; Yang Yang; Suying Ding; Qian Qin (Scientific Reports)
Abstract This longitudinal study sought to identify distinct body mass index (BMI) trajectories and investigate the impact of these level-independent BMI trajectories on the prevalence of thyroid nodules (TN). This study encompassed a cohort of 1967 participants from a hospital in China. Utilizing latent class growth mixture modeling (LCGMM), four BMI trajectory groups were identified based on the BMI of individuals without TN from 2017 to 2019. The occurrence of TN in participants was monitored from 2020 to 2021. BMI trajectory classes and age were considered potential risk factors for TN development. After adjusting for covariates, the odds ratios (ORs) of model-estimated BMI levels were confirmed in the 27-50-year age group, ranging from 1.077 (1.000–1.158) to 1.189 (1.072–1.319). Significant associations between model-estimated BMI slope and TN were observed in the 21-47-year-old age group, with ORs varying between 1.270 (1.014, 1.591) and 2.490 (1.004, 6.174). The level-independent BMI trajectories throughout life significantly influenced the risk of TN prevalence. Moreover, controlling BMI growth rate in early adulthood (27–47 years old) emerged as a critical age window for reducing TN prevalence, underscoring its importance in TN prevention strategies.